2013
DOI: 10.4028/www.scientific.net/amm.347-350.496
|View full text |Cite
|
Sign up to set email alerts
|

Control Law Design Based on Geometric Algebra

Abstract: A position and attitude control law is developed using geometric algebra (GA). GA is a powerful representational and computational system for geometry. The rigid body motion can be represented by the versor product in GA framework. Using the kinematics of the motor (the versor which represents the rigid body motion in GA), the control law of the rigid body motion can be developed. This paper provides a GA-based position and attitude control law by using the negative feedback of the motor. The stability of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
0
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 6 publications
(10 reference statements)
0
0
0
Order By: Relevance
“…The proportional control law which transfers the rigid body to the equilibrium point can be formulated in GA as [7] 1…”
Section: Control Law Designmentioning
confidence: 99%
See 3 more Smart Citations
“…The proportional control law which transfers the rigid body to the equilibrium point can be formulated in GA as [7] 1…”
Section: Control Law Designmentioning
confidence: 99%
“…Suppose that the ideal position and attitude of a rigid body is d M , and the actual position and attitude of it is M , the error between them can then be written as (12) It is shown that the system is stable when using the negative feedback of the motor, i.e. [7]…”
Section: Control Law Designmentioning
confidence: 99%
See 2 more Smart Citations